2018
DOI: 10.1097/igc.0000000000001346
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Features of Recurrent Endometrial Cancer in Japan: Chemotherapy Instead of Radiotherapy as Postoperative Adjuvant Treatment

Abstract: Adjuvant chemotherapy was insufficient to reduce the incidence of distant recurrence. The prognosis of patients recurred within regional LN and/or vagina was significantly better than that of patients with recurrence in other lesions because of treatment with surgery and/or radiotherapy. The disease-free interval was a significant prognostic factor for REC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Currently, the conventional treatment of EC is mainly surgery, radiotherapy, and chemotherapy. 7 Unfortunately, the 5-year overall survival rate of EC with advanced stage is only 15% to 17%. 8 Therefore, it is urgently necessary to seek out reliable diagnostic and prognostic biomarkers and novel treatment strategies for EC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the conventional treatment of EC is mainly surgery, radiotherapy, and chemotherapy. 7 Unfortunately, the 5-year overall survival rate of EC with advanced stage is only 15% to 17%. 8 Therefore, it is urgently necessary to seek out reliable diagnostic and prognostic biomarkers and novel treatment strategies for EC.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, age, and late menopause have been proposed as several risk factors for EC, 5,6 but the specific mechanism that causes the disease is still not clear. Currently, the conventional treatment of EC is mainly surgery, radiotherapy, and chemotherapy 7 . Unfortunately, the 5‐year overall survival rate of EC with advanced stage is only 15% to 17% 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Its morbidity and mortality have presented an ascending trend in the last few years, and it is reported that it occurs over a wide range of age groups from young individuals to elderly women 1,2. Surgery, chemotherapy, and radiotherapy have been considered as effective treatments for EC 3,4. Alternatively, an increasing number of investigators have focused more attention on exploring and elaborating the pathogenic mechanisms of development and progression of EC 5.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Erkilinç et al, (2018) reported that the presence of adenomyosis was associated with higher overall survival (HR = 0.20; 95% CI, 0.03-0.68). A possible explanation for these results is that most participants in our study received adjuvant treatment, which can reduce tumor recurrence (Eggink et al, 2017;Iwase et al, 2018;Qu et al, 2018). In this study, patients received adjuvant treatment about 66% of all patients.…”
Section: Discussionmentioning
confidence: 83%